Impact evaluation of a new counselling and support programme for unemployed with multiple placement obstacles - René Böheim; Rainer Eppel; Helmut Mahringer (Austrian Institute of Economic Research (WIFO), 2024)
We analysed a new counselling and support programme for people with low employment prospects in Austria. The Austrian Public Employment Service introduced regional pilots to investigate whether a new counselling strategy could improve labour market outcomes for this group. Eligible unemployed individuals could opt for third-party counselling and support, access a wide range of low-threshold services, and focus on personal stability rather than job placement. The goal was to achieve similar or even better labour market outcomes at lower cost. By comparing pilot and control regions, we found that introducing the offer resulted in higher costs without improving labour market outcomes.
Keywords: J64; J68; 330; Long-term unemployment; active labour market policy; Public EmploymentService; counselling; job placement